Do agglomeration economies affect the local comovement of stock returns? Evidence from China. (April 2017) - Firth, Michael; Fu, Shihe; Shan, Liwei
Prior studies in finance have examined the comovement of stock returns of firms headquartered in the same location. One interpretation of the results is that local investors have a 'local bias' due to an information advantage on local firms. We propose that localised agglomeration economies affect the fundamentals of local firms, resulting in the local comovement of stock returns. Using data for China A-share listed firms from 1997 to 2007, we find evidence of the comovement of stock returns of Chinese firms headquartered in the same city. We find inconsistent evidence for the local bias theory. The comovement of the stock returns of firms headquartered in the same city is stronger when the agglomeration economies in the city are stronger, suggesting that localised agglomeration economies provide an alternative explanation of the comovement of stock returns.